Unravelling microbial populations and volatile organic compounds of artisan fermented liver sausages manufactured in Central Italy. (April 2022) - Belleggia, Luca; Ferrocino, Ilario; Reale, Anna; Haouet, M. Naceur; Corvaglia, Maria Rita; Milanović, Vesna; Boscaino, Floriana; Di Renzo, Tiziana; Di Bella, Sara; Borghi, Monica; Farneti, Silvana; Cesaro, Cristiana; et al.
Graphical abstract: Highlights: Fermented liver sausages collected from twenty artisan producers were studied. The bacterial biota displayed the highest frequency (80%) of Latilactobacillus sakei. Debaryomyces hansenii, Staphylococcus xylosus, Staphylococcus equorum were found. Main volatiles included terpenoids, aldehydes, ketones, alcohols, esters, and acids. Hepatitis E virus assessed via real-time-RT-(q)PCR assay was never detected. Abstract: The aim of the present study was to obtain information on the occurrence of bacteria and eumycetes in ready-to-eat fermented liver sausages manufactured by 20 artisan producers located in the Marche Region (Italy). To this end, culture-dependent analyses and metataxonomic sequencing were carried out. Physico-chemical parameters and volatilome of the fermented liver sausages were also studied. Finally, the presence of hepatitis E virus (HEV) was also assessed via real-time-RT-(q)PCR assays. Active microbial populations mainly represented by lactic acid bacteria, enterococci, coagulase-negative cocci, and eumycetes were detected. Enterobacteriaceae, Pseudomonadaceae, and sulfite-reducing anaerobes were not detected in most of the samples. Latilactobacillus sakei dominated in all the analyzed samples, reaching abundances up to 80%. Staphylococcus xylosus and Staphylococcus equorum were also detected. Among minority bacterial taxa, Weissella spp., Leuconostoc spp., Macrococcus caseolyticus, Brochothrix thermosphacta, Staphylococcus succinus, Lactobacillus coryniformis, Lactiplantibacillus plantarum, Lactococcus garviae, Psychrobacter spp ., and Carnobacterium viridans were detected. The mycobiota was mainly composed by Debaryomyces hansenii that was present in all samples at the highest frequency. Among minority fungal taxa, Aspergillus spp., Penicillium spp., Kurtzmaniella zeylanoides, Candida spp., Yamadazyma spp., Scopulariopsis spp., Yarrowia spp., and Starmerella spp. were detected. Interestingly, associations between some taxa and some physico-chemical parameters were also discovered. The absence of HEV in all the samples attested a high level of safety. Finally, most of the VOCs detected in the analyzed fermented liver sausages belonged to six classes as: terpenoids, aldehydes, ketones, alcohols, esters, and acids. Nitrogen compounds, sulfur compounds, phenols, hydrocarbons, lactones, furans, and aromatic hydrocarbons were also identified. Several significant relationships were observed between mycobiota and VOCs.